VR table tennis opponent - Sim, Davis Kwan Hong (Nanyang Technological University, 2023)
This project focuses on implementing Inverse Kinematics (IK) on a 3D table tennis player model to enhance its animation and provide a more immersive gaming experience. The IK is employed to estimate poses without the need for tracking data. By employing IK, the player model's arm dynamically follows the ping-pong paddle's movements, allowing for more immersive gameplay. Through the process of rigging and setting up avatar masks, the model's upper and lower body movements are procedurally animated with the help of IK. This allows for dynamic steps and arm movements in response to the paddle's position and orientation. The project also addresses challenges in configuring Unity's animation system and applying constraints for body movements. Throughout the development process, challenges included addressing squatting posture issues, refining the rig setup, and managing constraints for natural joint movements. The project achieves the goal of providing a more immersive VR table tennis experience with a fully animated 3D player model. Future improvements could involve implementing additional restraints for finer joint control, refining side-step motions, incorporating AI-controlled paddle movements, and enhancing the visual quality of the 3D model. Overall, this project demonstrates the application of IK to enhance gameplay, opening avenues for further advancements in virtual sports simulations.